PENGEMBANGAN MEDIA PEMBELAJARAN MENGGUNAKAN GEOGEBRA PADA SUB POKOK BAHASAN GARIS SINGGUNG PERSEKUTUAN DUA LINGKARAN - Rohmawati, Elok; Kristanto, Vigih Hery (UNIVERSITAS RIAU KEPULAUAN, BATAM, INDONESIA, 2018)
This research is a development research that aims to to find out the process and result of development of learning media of mathematics using Geogebra on sub subject of tangent alliance of two circles. Supporting devices used are RPP, BKS, BPG, and THB. The chosen development stage is Research and Development (R D) which has been modified by adding Nieveen criteria that is valid, practical and effective. Data collection techniques used questionnaires, observation sheets and tests. According to the criteria of practicality, it is known that the questionnaire of ease of using media reaches 79.8%. The operation of this media is so easy that it's easy to remember and can be used as a tool to learn the material. Questionnaires the role of teachers reached 81%. By using the teacher's activity media in explaining the material to be a little, because the students are more observing, summing up opinions, and working on the problem, so the teacher's interaction with the students is minimal, and the material explanation is enough to use the media. Observation sheet minimizes teacher's role by 76.95%. From the observer observation the students observed more, no difficulties in the use of media. However, learning cannot be finished as in RPP. According to the effectiveness criteria seen from the test of student learning outcomes so that the mastery of classical reach 35%. This is because learning is too focused on observation and discovery of the formula so that students do not practice in doing the problem. From this research, there are several findings, namely: learning media using Geogebra, supporting tool, namely RPP, BKS, BPG, THB and instrument have validity level on valid criteria, learning media using Geogebra is easy to use, learning media using Geogebra with supporting device can minimize the role of teachers so that the media meet the practical criteria. The test of learning outcomes has not been completed in a classical manner because the classical completeness does not reach 75% upwards, meaning that the media has not met the effective criteria.